Dampak Dari Penambangan Timah Inkonvensional Di Desa Lampur Kabupaten Bangka Tengah - Citra Asmara Indra (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2013)
Lampur village is an area that still has a lot of Tin deposits are characterized by the emergence of a lead-mining-camp camp inkonvensial at many points in this area. Lampur indeed simply a village administratively, but became a mixture of the two districts and some districts. In 2001, when the autonomous region and the rampant mining it, the village became the main destination Lampur miners entrants to dig the Tin. The impact of the change in behavior IT mining village community consumer as well as being perceived Lampur also by the school, when many students are reduced because they prefer to seek fortune in the location of it and the fact it was left by its parents resulting in increased dropout rates.